Hubungan Motivasi dan Budaya Organisasi Terhadap Kinerja Pegawai BKKBN Provinsi Jawa Tengah - Nindias, Ruri Dwi; Subowo, Ari; Rihandoyo, Rihandoyo (Journal of Public Policy and Management Review, 2015)
Human resources is one factor that has an important role in improving employee performance. Given the importance of human resources, it is a company or organization must pay attention to the factors that affect human resources work. Organizational culture and motivation affect the performance of employees in accordance with procedures and increase employee performance. This research was conducted in the city of Semarang. Samples were taken by using simple random sampling technique. Methods of data collection is done by using a questionnaire distributed to respondents who work in Central Java Province BKKBN office. The data obtained in this study were analyzed using multiple linear regression analysis. These results indicate that the variables of motivation and organizational culture has a positive and significant impact on employee performance. With the positive influence of organizational culture and motivation can improve employee performance.